Educational Administrators’ Views on their Awareness about Educational Planning - Bayram, Arslan (2021)
The purpose of this research was to determine administrators’ views on their awareness of educational planning, purpose, benefits and problems they encounter with it. It was also aimed to find out if the administrators received education and training in educational planning. The research employed a qualitative phenomenological research design. The participants were 15 administrators who were determined with a maximum diversity method. The data were gathered with semi-structured interview technique and analyzed with descriptive analysis approach. Results revealed that most administrators received in-service training or education in educational planning, underlined numerous benefits, and they are aware of the importance of it. It was also discovered that although some administrators encounter problems, they consider educational planning as an important tool to achieve organizational goals.